Determination of selenium in biological materials by short-time neutron activation analysis using ⁷⁷ᵐSe at the Dalat research reactor - Ho , Van Doanh; Tran , Quang Thien; Nguyen , Thi Sy; Nguyen , Nhi Dien (Nuclear Science and Technology, 2014)
A rapid neutron activation analysis technique for determination of the concentration of selenium in biological materials using short-lived radionuclide 77mSe (half-life = 17.4 seconds) has been developed at Dalat Nuclear Research Institute (DNRI). The technique is very simple and rapid. It involves irradiation of a sample for 20 s, decay for 20 s and counting for 20 s. The accuracy of the method has been evaluated by analyzing a number of biological standard reference materials of varied selenium levels. An agreement between measured and certified values was acceptable in regarding to the deviation of the above mentioned two values within 8 percent. The result shows that the utilization of short-lived radionuclide 77mSe is more useful in comparison with long-lived radionuclide 75Se (half-life = 120 days). In addition, it is suggested that a further study for cyclic irradiations should be done in order to enhance the detection limit of the determination of the short-lived radionuclide 77mSe.